Plant diversity on coffee agroforestry land in the buffer zone of Bromo Tengger Semeru National Park in East Java, Indonesia - HASAN ZAYADI; LUCHMAN HAKIM; SUDARTO SUDARTO; JATI BATORO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Zayadi H, Hakim L, Sudarto, Batoro J. 2024. Plant diversity on coffee agroforestry land in the buffer zone of Bromo Tengger Semeru National Park in East Java, Indonesia. Biodiversitas 25: 1030-1036. Bromo Tengger Semeru National Park (BTSNP) is facing threats to biodiversity due to land transfer functions and sand mining in rural areas. Land use conversion and sand mining in rural areas near BTSNP and Perhutani are threatening biodiversity through activities like land degradation, deforestation, forest depletion, and global climate change impacting local agriculture. Coffee farms in Poncokusumo and Wajak have been abandoned, leading to a decline in coffee farming and other agricultural commodities. Coffee-based agroforestry systems have been implemented to address this issue and improve soil fertility and vegetation diversity. This research aimed to identify and analyze plant diversity in coffee agroforestry land in BTNSP. The study was carried out in January-December 2022 in the village districts of Poncokusumo Sub-district (Sumberejo) and Wajak Sub-district of Malang District, which borders directly with BTSNP, collecting flora compositions and classifying them based on growth rate. The study identified 27 orders, 38 families, and 71 species of plants in the coffee fields. The presence of various plant species in the coffee fields contributes to the ecosystem's stability and the soil's quality. This research highlights the importance of the agroforestry system in promoting biodiversity conservation and sustainable coffee farming in the BTSNP area.